2017
DOI: 10.1186/s13065-017-0283-3
|View full text |Cite
|
Sign up to set email alerts
|

Hemostatic chemical constituents from natural medicine Toddalia asiatica root bark by LC-ESI Q-TOF MSE

Abstract: Background Toddalia asiatica root bark as an effective hemostatic natural medicine or Chinese materia medica was applied in China for long history, its complex drug action mechanisms and unclear substance basis have been constraining the development of this drug.ResultsAn intelligentized strategy by LC-ESI Q-TOF MSE was presented in this study for rapid identification of hemostatic chemical constituents from this natural medicine. Chromatographic separation was performed on a C18 column (150 mm × 2.1 mm, 1.8 μ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 9 publications
2
15
0
Order By: Relevance
“…This was evident in the secondary mass spectra (fragment ions at m/z 232.04, 203.03, and 187.04). The molecular weight of compound 2 was consistent with that reported previously for isopimpinellin .…”
Section: Resultssupporting
confidence: 90%
“…This was evident in the secondary mass spectra (fragment ions at m/z 232.04, 203.03, and 187.04). The molecular weight of compound 2 was consistent with that reported previously for isopimpinellin .…”
Section: Resultssupporting
confidence: 90%
“…(Rutaceae) (Syn: Toddalia aculeata Pers., Scopolia aculeata Sm., Paullinia asiatica L.), well known as Feilongzhangxue in Chinese and commonly known as orange climber in English, is widely distributed in the east, south, and southeast of Asia, Madagascar, Africa, and the Mascarene Islands [1,2]. The roots and barks of T. asiatica have been used in Miao minority medicine, mainly in Guizhou, Yunnan, and Guangxi provinces in China, for the treatment of fall injuries, rheumatic arthralgia, stomachache, chronic lumbago, and diarrhea [3,4]. Previous phytochemical and pharmacological investigations of different parts of this plant revealed that coumarins are the main secondary metabolites [5], some of which exhibited cytotoxic, antimalarial [6], antiviral [7], anti-inflammatory [8], antibacterial [9], anti-platelet aggregation [10], anti-plasmodial, larvicidal [11], phosphodiesterase-4 inhibitory [12], and osteoclastogenesis activities [13].…”
Section: Introductionmentioning
confidence: 99%
“…Ten compounds were unambiguously identified as chlorogenic acid, ferulic acid, nodakenin, bergapten, 3,4‐dicaffeoylquinic acid, 3,5‐dicaffeoylquinic acid, 4,5‐dicaffeoylquinic acid, imperatorin, notopterol and isoimperatorin (peaks 6, 16, 17, 18, 21, 22, 34, 38, 42 and 44, respectively) based on the retention time and mass spectra of these standards. The identification of other compounds was deduced by reference to previously published data, performing accurate m / z value analysis of the TOF‐MS data, and with QTOF‐MS/MS fragment analysis. All detected compounds are shown in Table .…”
Section: Resultsmentioning
confidence: 99%